The impact of inpatient collaborative clinical pharmacy renal dosing service on dosage adjustment in patients with chronic kidney disease [RS1-441]. - Abdulhafez Khatib (Al-Ramahi), Rowa Jamal (2009)

(untitled)
Pesakit ginjal kronik sering mengalami perubahan farmakokinetik dan gerak balas farmakodinamik.